Gender Discrimination in Employment: BRICS Countries Overview - E. Sychenko; M. Laruccia; D. Cusciano; R. Korde; K. Nagadia; I. Chikireva; J. Wang; N. Carrim (BRICS Law Journal, 2022)
This article investigates the phenomenon of gender equality in employment in the BRICS countries where it is one of the factors hampering the economic development and basic human rights. The authors examine the international obligations of these states under the human rights treaties of the United Nations Organization (UNO) and the International Labour Organization (ILO), compare the national anti-discriminatory norms with the international standards (ILO Conventions and the Convention on the Elimination of all Forms of Discrimination Against Women) and evaluate the observations of the relevant international bodies recently adopted in respect of the BRICS states. In particular, the activities of the Committee on the Elimination of Discrimination Against Women and the ILO Committee of Experts on the Application of Conventions and Recommendations are reviewed. In the paragraphs that follow, the national legislation and case-laws are examined. Furthermore, the reasons for the persistent gender stereotypes in the labor market, as well as the general attitude toward women’s roles in society in each country are reviewed. The authors identify the obstacles to achieving true gender equality in the workplace and formulate recommendations for improving protections against discrimination of women in employment as well as ensuring equal access to employment and promotion.